فاعلية الخرائط الذهنية في تحصيل طلاب المرحلة الاعدادية لمادة التربية الاسلامية - حسين فرج المصلحي, علاء (Journal of College of Education, 2019)
The aim of this research is to know the effectiveness of mental maps on the achievement of students in the fifth grade in Islamic education.(33) students studied using the map (33) students studied using the mapThe researcher was rewarded between the two groups in the variables of scholastic achievement of the parents and the age of the students calculated by months.The researcher formulated 50 behavioral goals and prepared unprecedented teaching plans in light of the content of the book and the behavioral goals formulated. The researcher prepared a collection test consisting of (20) paragraphs